Karakterisasi dan Klasifikasi Ultisols Yang Berkembang dari Dua Bahan Induk di Kabupaten Serang, Provinsi Banten - Mahfud Arifin; Ganjar Herdiansyah; Apong Sandrawati; Rina Devnita (Soilrens, 2021)
The effort to utilize the soils optimally, especially Ultisols, requires an appropriate understanding related to their characteristics. The characteristics of Ultisols are sturdily influenced by soil-forming factors, viz. climate, parent material, pedogenic age and topography. The purposes of this study were to determine the chemical, physical, mineralogical characteristics and soil development classification level of Ultisol from two different types of parent rock. This research was conducted in Kampungbaru Village, Petir District and Sukalaksana Village, Curug District, in Serang Regency, Banten Province. These two villages represented different parent materials, namely andesite lava parent material of Holocene age (Kampungbaru Village) and tuff dacite parent material of early Pleistocene age (Sukalaksana Village). The research method was descriptive, comparative and survey. Soil classification was based on the Soil Survey Staff. The results showed that Ultisols developed from dacite tuff and andesite lava did not show contrasting differences in soil properties. The level of weathering of the two pedons was at the senile stage and the level of soil development of the two pedons was at the argillic stage. The soil classification of Kampungbaru pedon was Typic Palehumults, very fine, kaolinitic, isohyperthermic, while the Sukalaksana pedons was Arenic Paleudults, fine, kaolinitic, isohyperthermic